Reaction Kinetics in Conversion Process of Pineapple Leaves into Glucose - Muhaimin Muhaimin; Beta Wulan Febriana; Septian Arfan (Reaktor, 2018)
Abstract This research aimed to determine the reaction kinetics in the process of hydrolysis of pineapple leaves. The experiment was carried out at the temperature (60, 90, and 120 oC) and variation of acid catalyst concentration (0.1; 0.5 and 1 M) by observation reaction time every 30 min. The kinetics model of hydrolysis reactions of pineapple leaves has shown first order reaction with activation energy value to find the concentration of sulfuric acid successively: 0.1 M; -15420 KJ/mol; 0,5 M; 3173.8 KJ/mol; 1 M; 100.53 KJ/mol. The reaction rate constant which produced the highest glucose level was on the use of sulfuric acid at a concentration of 0.1 M at a temperature of 120 oC with glucose levels produced between 26.366.039 ppm to 155.510.778 ppm with k = 0.0106/min. Keywords: glucose; hydrolysis; kinetic model; pineapple leaves